FOOD PRODUCTION AND SOLID WASTE GENERATION: A COMPARATIVE STUDY BETWEEN TWO INDUSTRIAL KITCHENS IN NORTHERN SANTA CATARINA - Novais da Silva, Fernando; Zimmermann, Guilherme; Amaral Reinert, Kamili; Defrein, Talita; dos Anjos Geiza, Andrea (Revista Gênero e Interdisciplinaridade, 2025)
This case study presents a comparative analysis of meal production and waste generation in two industrial kitchens of different sizes, located in northern Santa Catarina and operated by the company Maná do Brasil. Industrial Kitchen 1 (Itapoá), a large-scale unit (approx. 1,600 employees, 500 diners), and Industrial Kitchen 2 (Joinville), a medium-scale unit (approx. 280 employees), were evaluated through the collection and quantitative analysis of waste data. The categories examined were: pre-preparation waste, plate waste, clean leftovers, and inventory losses. The study aligns with the global urgency of Sustainable Development Goal (SDG) 12.3, which aims to halve food waste by 2030 (United Nations, 2015). Significant differences were identified in waste patterns, with both kitchens showing substantial absolute waste volumes. When sent to landfills, such waste generates severe environmental impacts, including methane emissions. The study discusses the drivers of these variations and highlights the importance of adopting operational practices consistent with Circular Economy (CE) principles and ESG (Environmental, Social, and Governance) guidelines (Torquato, 2023). The findings indicate that effective reduction requires tailored management strategies, process optimization, and awareness initiatives to support responsible consumption and production (SDG 12).